Odonata type specimens preserved in the Museo de La Plata - Muzon, Javier (2007)
Type collection preserved at Museo de La Plata includes 105 specimens of Odonata (6 holotypes, 1 neotype, 6 allotypes and 96 paratypes), representing 13 names belonging to Coenagrionidae (5), Lestidae (1), Megapodagrionidae (I), Aeshnidae (4), Gomphidae (1) and Libellulidae (1). Preservation status and label details ofprimary types are stated.